Hubungan Antara Pengetahuan dan Sikap dengan Perilaku Pencegahan COVID-19 Pada Peserta Seminar Online STIKes Raflesia 7 April 2020 - Gunawan, Susilawati; Sinsin, Iis; Zani, Andri Yan Prima (UI Scholars Hub, 2021)
Introduction. Early in 2020, the world was shocked by the COVID-19 pandemic. The increasing number of cases was fast and spread to various countries. The rapid spread and the number of cases increasing have resulted in the importance of socialization and education on preventing and controlling this infectious disease. The community must play a role in breaking the chain of COVID-19 transmission by implementing health protocols. Objective. to find out the knowledge, attitudes and practices of the community to prevent the spread of the COVID-19 Methods. used a quantitative approach with a cross-sectional design by distributing questionnaires online using the google form platform to the participants of the COVID-19 Seminar at STIKes Raflesia Depok. The population is all participants of the COVID-19 seminar at STIKes Raflesia on 7 th April 2020, totaling 310 participants. Thus, the sample was 260 participants who filled out the questionnaire completely. Data analysis used multivariate multiple logistic regression test. Results. The survey results showed that the respondents' knowledge about COVID19 was 71.2% good, the attitude showed 74.6% positive and the respondent's behavior showed 59.2% well Conclusion. There was no significant relationship between good knowledge resulting in a positive attitude and good behavior in preventing COVID-19.